Highly Tunable Nanostructures in a Doubly pH‐Responsive Pentablock Terpolymer in Solution and in Thin Films. (3rd June 2021) - Jung, Florian A.; Schart, Maximilian; Bührend, Lukas; Meidinger, Elisabeth; Kang, Jia‐Jhen; Niebuur, Bart‐Jan; Ariaee, Sina; Molodenskiy, Dmitry S.; Posselt, Dorthe; Amenitsch, Heinz; Tsitsilianis, Constantinos; Papadakis, Christine M.
Abstract: Multiblock copolymers with charged blocks are complex systems that show great potential for enhancing the structural control of block copolymers. A pentablock terpolymer PMMA‐ b ‐PDMAEMA‐ b ‐P2VP‐ b ‐PDMAEMA‐ b ‐PMMA is investigated. It contains two types of midblocks, which are weak cationic polyelectrolytes, namely poly(2‐(dimethylamino)ethyl methacrylate) (PDMAEMA) and poly(2‐vinylpyridine) (P2VP). Furthermore, these are end‐capped with short hydrophobic poly(methyl methacrylate) (PMMA) blocks in dilute aqueous solution and thin films. The self‐assembly behavior depends on the degrees of ionization α of the P2VP and PDMAEMA blocks, which are altered in a wide range by varying the pH value. High degrees of ionization of both blocks prevent structure formation, whereas microphase‐separated nanostructures form for a partially charged and uncharged state. While in solutions, the nanostructure formation is governed by the dependence of the P2VP block solubility of the and the flexibility of the PDMAEMA blocks on α, in thin films, the dependence of the segregation strength on α is key. Furthermore, the solution state plays a crucial role in the film formation during spin‐coating. Overall, both the mixing behavior of the 3 types of blocks and the block sequence, governing the bridging behavior, result in strong variations of the nanostructures and their repeat distances. Abstract : Multiblock polymers containing charged segments yield excellent control of nanostructures formed by self‐assembly. The use of two distinct polyelectrolyte blocks in a pentablock terpolymer allows studying the morphologies in dependence on the charge distribution by varying the pH value. Multiple interactions and mechanisms underlying the nanostructure formation are identified in solutions and thin films.